We are given the following two equations
![\begin{gathered} 3x+y=-5\quad eq.1 \\ 6x+2y=10\quad eq.2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hqgxcbyg8i5fjljus8c2cm1swe5pk3pc8f.png)
Let us solve the system of equations using the substitution method.
Separate out one of the variables in any of the two equations
Let us separate out x from eq.1
![\begin{gathered} 3x+y=-5 \\ 3x=-5-5 \\ x=(-y-5)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9cf00ntq778dhyla2kjlgy030jtftr0pcq.png)
Now, substitute this value of x into eq.2
![\begin{gathered} 6x+2y=10\quad eq.2 \\ 6((-y-5)/(3))_{}+2y=10 \\ 2(-y-5)_{}+2y=10 \\ -2y-10+2y=10 \\ -10=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/72lhj2z1fm5a3sfmoxh78ebtxs24sqo9bk.png)
The variable y also got canceled and we are left with something that cannot be true. (-10 cannot be equal to 10)
This means that the system of equations has infinitely many solutions.